Pengaruh Senam Asma Terhadap Kemampuan Pernapasan Penderita Asma Di Poli Asma RSUD Bangil - Kusuma, Erik; Herlambang, Bayu (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2020)
Asthma was a chronic imflammatory disorder that causes bronchospasm and bronchoconstriction which can cause respiratory muscles to experience weakness, resulting in the decreased of respiratory ability. Asthma exercise improves respiratory ability in asthma disorders. This study aims to identify the effect of asthma exercise on the respiratory ability of asthma patients at Asthma Poly Bangil Regional General Hospital. This type of research is pre experiment with pre test-post test design. The sampling technique uses total sampling so that the number of samples were 31 people. Data analysis using statistical test t test bound with a significant level of Î± : 0.05. The results showed the average respiratory ability (APE) before asthma exercise were 208 lt / min gymnastics and after asthma exercise increased to 304 lt / min, a statistical test obtained p value: 0,000 (<Î±: 0,05) there was an asthma exercise effect on the respiratory ability in asthma patients at Asthma Poly Bangil Regional General Hospital. It is recommended for asthmatics to carry out asthma exercises regularly in order to improve their breathing ability and improve the quality of life.Keywords: Asthma Exercise, Respiratory Ability